Genetic and environmental effects on tonic immobility duration of red-winged tinamou applying survival analysis - Hata, Milene Elissa [UNESP]; Caetano, S. L. [UNESP]; Boleli, I. C. [UNESP]; Queiroz, S. A. [UNESP] (FapUNIFESP (SciELO), 2018)
Fear behavioral studies provide knowledge on animal welfare, and fearful behaviors can be used as selection criteria of individuals adapted to intensive rearing system. The survival analysis methodology was applied to estimate tonic immobility (TI) duration, as an indicator of fear, of red-winged tinamous (Rhynchotus rufescens) reared in captivity and to determine if TI is genetically influenced. A number of 539 birds born between 2006 and 2010 were evaluated. The exploratory data analysis was performed using the Kaplan-Meier estimate (KM), and the covariates were then fit to a Cox model, considering month of observation nested within year of birth and body weight as fixed effects and the random effect of sire as frailty term. In order to predict genetic values and to estimate heritability, the model of proportional hazards was applied, using a Weibull distribution as the baseline hazard. Birds born in the last year presented shorter TI duration than those born in the previous year, as shown by the survival KM curves, indicating a decline in fearfulness from one year to the next. The Cox analysis detected that hazard function was reduced as body weight increased. The frailty term was significant (p<0.05), showing that sires induced variation in the TI duration of the offspring. Heritability estimated as 0.37, indicating the influence of additive genes. These findings suggest that the selection of for short TI duration may allow reducing fearfulness of a red-winged tinamou population after some generations.
Keywords: Animal welfare; Behavioral trait; Genetic; Parameters; Survival kit; Wild birds